UPAYA KELUARGA ORANGTUA TUNGGAL DALAM MEMPERTAHANKAN EKONOMI KELUARGA DI KELURAHAN KOTA LAMA KECAMATAN KUNTO DARUSSALAM KABUPATEN ROKAN HULU - Utari, Riski; ", M. Razif (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Berorang growth of single-parent families is now ongoing phenomenon . Kotalama in the Village , District Kunto Darussalam , Rokan Hulu occurrence of single parent due to divorce and the death of one spouse . Causes of single parent families are: a ) divorced , widowed status generally affected in a number of factors working in her husband's inadequate and can not fulfill the economic needs of the family . b ) divorce die , as with the factors of pain on a partner or husband and this is becoming a status be left for dead by his partner 's widow . c ) there are also factors that cheating on a spouse is a single parent , choose to live with another woman and this is what makes the status of a single parent or widow . Due to the two parties to which it damages the relationship in a single parent . In this study population taken is the number of single parent women in urban cities than 5 respondents . In general, 5 of a sample of respondents is low on economic factors and education below high school education . The number of samples taken in engineering the population quota ( quota sampling ) that is the size of samples taken for each category in proportion to the actual population for each category . The number of single parents are divorced divided into 3 and 2 couples stayed dead . And part of a single parent is 2 respondents in the medium and low economic factors 3 respondents made infoman .In this research, using qualitative descriptive research model . Research subjects in this study were single parent families and in this case the researchers took samples with both techniques quota ( quota sampling ) that is the size of samples taken for each category in proportion to the actual population for each category . Instruments used are filtering the data are interview , observation and documentation . The technique of data analysis used descriptive qualitative . Public distrust in the success of parenting and to meet the needs of families in single parent families is quite high . So that seeks to maintain the single parent family economy . The theory used for the formulation of the problem of single parents to survive by working outside the home is the theory that Emile Durkheim theory of social capital .Keywords : single parent , social capital ( building relationships fellow , and maintain ,able to work or achieve various things achieved but with difficulty ) .